Desain Hybrid Prototype System Deteksi Api dan Deteksi Gerak Pada Keamanan Ruangan - Shoffin Nahwa Utama (Fountain of Informatics Journal, 2016)
The use of surveillance cameras are commonly used in place or room that is considered vulnerable, not only monitor but also can provide a sense of security for its users. This study discusses concerning fire detection and motion detection using a webcam for security room. Fire detection using the method of fire threshold RGB values by comparing each frame images captured by the webcam as data input, at the motion detection algorithm using blob calculation. Warning system used SMS gateway and sent to the specified server. The results show the value range RGB flame 218-248, 240-250, 242-252 and the use of motion detection complementary security systems built.